La partecipazione democratica fra narrazione neoliberista e opportunità di inclusione - Sorice, Michele (Studi Politici, 2022)
The article discusses the ambiguities of the concept and practices of democratic participation, situating it within neoliberalism. It identifies some critical elements: from the bipartition between conventional and non-conventional participation to the hyper-optimistic and uncritical rhetoric that has accompanied the success of digital communication ecosystems. The rhetoric on the supposed potential of the digital relates to the development of “participationism”, that is a social narrative that exalts a neutral and non-conflictual dimension of participation, and which goes hand in hand with the processes of depoliticisation, typical of neoliberalism. Considering participation as a political principle means, on the other hand, reconsidering the link between political participation and community building, as well as identifying participatory processes as necessary tools for fostering social inclusion.